Retraction notice : DEVELOPMENT AND APPLICATION OF INQUIRY-BASED SCIENCE ASSESSMENT QUESTIONS FOR ELEMENTARY STUDENTS (III) - Kong Young Tae (European Scientific Journal, ESJ, 2014)
The purpose of this study is to incorporate inquiry-based questions in science assessment and analyzes student responses in purpose of evaluating scientific inquiry abilities of 5th and 6th grade students in Korea. It also aims to assess students’ performances on inquiry-based evaluation and to develop guidance on teaching for development of inquiry skills. This study mainly reports the result about a biology content domain.For this purpose, the chosen research subjects were 1,198 fifth and sixth graders from seven elementary schools in Woolsan and Gyeongsangnam-Do. The assessment questions was designed and applied to the elementary schools by modifying and reinforcing the NAAA (National Assessment of Academic Ability) developed by NIER (National Institute for Educational Policy Research of Japan) to incorporate inquiry-based learning and correspond to 2007 amendment of national science education curriculum in Korea.From this study, it was observed that students’ scientific inquiry abilities and misconceptions in biology domain were obtained through the development and application of inquiry-based assessment questions, and teaching approaches for increasing students’ inquiry skills were also obtained.